Analisis faktor eksploratori dan analisis faktor konfirmatori skala Male Role Norms Inventory-Short Form - Isaputra, Samuel Adiprasetya; Chandra, Rachel Theophilia; Himawan, Karel Karsten (Konsorsium Psikologi Ilmiah Nusantara, 2024)
The Male Role Norms Inventory-Short Form (MRNI-SF) scale is a widely used international scale for measuring traditional masculinity ideaology. Recently, it has begun to be utilized in Indonesia, where significant gender disparities in access to education and employment persist. Despite its increasing use, there is a notable lack of research specifically addressing the psychometric properties of the Indonesian adaptation of the MRNI-SF. This study aims to evaluate the validity and reliability of the Indonesian version of the MRNI-SF. Data were collected from a total of 346 student participants at various universities in Indonesia and analyzed using Exploratory Factor Analysis (EF) and Confirmatory Factor Analysis (CFA). The indicates that the Indonesian version of the MRNI-SF Scale accurately and reliably measure traditional masculinity ideology within the Indonesian context. Furthermore, the results show a high degree of similarity between the Indonesian version and the original scale.